Draft Genome Sequence of Clostridium tyrobutyricum Strain DIVETGP, Isolated from Cow’s Milk for Grana Padano Production - Soggiu, Alessio (Genome Announc, 2015)
We announce the draft genome sequence of Clostridium tyrobutyricum strain DIVETGP. This strain was isolated from cow’s milk used for Grana Padano cheese production. The genome was obtained using Illumina HiSeq technology and comprises 45 contigs for 3,018,999 bp, with a G+C content of 30.8%.